2014
DOI: 10.4085/1062-6059-49.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Postinjury Anxiety and Social Support Among Collegiate Athletes: A Comparison Between Orthopaedic Injuries and Concussions

Abstract: Both the concussed athletes and those with orthopaedic injuries experienced similar state and trait anxiety and relied on similar sources of social support postinjury. However, athletes with orthopaedic injuries reported greater satisfaction with support from all sources compared with concussed athletes. In contrast, concussed athletes showed more significant predictor models of social support on state anxiety at return to play.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 27 publications
4
107
0
1
Order By: Relevance
“…Algunos estudios proporcionaron resultados que sostenían que la familia fue la fuente más importante de apoyo social (Petrie et al, 2014;Covassin et al, 2014). Así, en el trabajo de Petrie et al (2014) se encontró que el apoyo social familiar junto con el bajo nivel de resistencia mental y el estrés producido por eventos positivos de la vida diaria, se relacionaba significativamente con el aumento de lesiones; es decir, que los deportistas que tienen bajos niveles de resistencia mental y de apoyo social familiar se lesionan con mayor frecuencia cuando experimentan altos niveles de estrés positivo.…”
Section: Introductionunclassified
“…Algunos estudios proporcionaron resultados que sostenían que la familia fue la fuente más importante de apoyo social (Petrie et al, 2014;Covassin et al, 2014). Así, en el trabajo de Petrie et al (2014) se encontró que el apoyo social familiar junto con el bajo nivel de resistencia mental y el estrés producido por eventos positivos de la vida diaria, se relacionaba significativamente con el aumento de lesiones; es decir, que los deportistas que tienen bajos niveles de resistencia mental y de apoyo social familiar se lesionan con mayor frecuencia cuando experimentan altos niveles de estrés positivo.…”
Section: Introductionunclassified
“…• One study 6 reported in athletes that greater social support was associated with decreased state-anxiety, and lower state anxiety postconcussion was associated with increased social support.…”
Section: Summary Of Search Best Evidencementioning
confidence: 99%
“…4 State anxiety refers to how a person feels in the current moment about various situations (ie, an injury). 6 Trait anxiety describes a personality characteristic focusing on a broad range of perceived threats. 4 Whereas, anxiety sensitivity is a personality trait where physiological, psychological, and social influences are perceived as threatening to oneself.…”
Section: Clinical Scenariomentioning
confidence: 99%
See 2 more Smart Citations